A bi‐allelic loss‐of‐function SARS1 variant in children with neurodevelopmental delay, deafness, cardiomyopathy, and decompensation during fever. Issue 12 (4th October 2021) - Ravel, Jean‐Marie; Dreumont, Natacha; Mosca, Pauline; Smith, Desiree E. C.; Mendes, Marisa I.; Wiedemann, Arnaud; Coelho, David; Schmitt, Emmanuelle; Rivière, Jean‐Baptiste; Tran Mau‐Them, Frédéric; Thevenon, Julien; Kuentz, Paul; et al.
Abstract: Aminoacyl‐tRNA synthetases (aaRS) are ubiquitously expressed enzymes responsible for ligating amino acids to their cognate tRNA molecules through an aminoacylation reaction. The resulting aminoacyl‐tRNA is delivered to ribosome elongation factors to participate in protein synthesis. Seryl‐tRNA synthetase (SARS1) is one of the cytosolic aaRSs and catalyzes serine attachment to tRNA Ser . SARS1 deficiency has already been associated with moderate intellectual disability, ataxia, muscle weakness, and seizure in one family. We describe here a new clinical presentation including developmental delay, central deafness, cardiomyopathy, and metabolic decompensation during fever leading to death, in a consanguineous Turkish family, with biallelic variants (c.638G>T, p.(Arg213Leu)) in SARS1 . This missense variant was shown to lead to protein instability, resulting in reduced protein level and enzymatic activity. Our results describe a new clinical entity and expand the clinical and mutational spectrum of SARS1 and aaRS deficiencies. Abstract : Aminoacyl‐tRNA synthetases (aaRS) are ubiquitously expressed enzymes responsible for ligating amino acids to their cognate tRNA molecules. We describe here a new clinical presentation including developmental delay, central deafness, cardiomyopathy, and metabolic decompensation during fever leading to death, in a consanguineous Turkish family, with biallelic variants (c.638G>T, p.(Arg213Leu)) in SARS1. This missense variant was shown to lead to protein instability, resulting in reduced protein level and enzymatic activity.